EDUCATION OF ELDERLY PEOPLE: INDIVIDUAL AND PUBLIC REQUEST - Тополь, О. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The role elderly people education in individual and social development is noted. Theoretical and methodological foundations of elderly people education are analyzed; the idea of lifelong learning in the historical and.